Estudo de caso retrospectivo longitudinal sobre o preço do leite no Rio Grande do Sul - Schneider, Catia Leticia Correa (2019)
With the growing demand for food, it is essential to adopt practices and technologies aimed at improving production efficiency, however the producer markets his production without knowing the price to be received per liter of milk, making investment difficult. Thus, the aim of this dissertation is to detail the importance of anticipating the price of milk to the producer, based on a joint council, for decision making and future investments in dairy activity. Producer revenue is directly influenced by the volume of milk traded, milk price and production cost. Seasonality is the main price variability, mainly related to the cost of food. The price of milk in the states of RS, SC, PR, has as reference the Joint Council Producers/Industry (CONSELEITE), which monthly discloses the reference values and projections of milk price for next month, which are separated into three standards. according to the goodwill and negative goodwill parameters, such as above-standard milk, standard milk and substandard milk, as set out in the normative instructions governing milk quality. The database for correlation analysis and multiple linear regression was formed by the values of CONSELEITE RS in the period 2008 - 2018, and data on milk production, composition and price of the Celeste Gobbato Technical State School - EETCG in the period 2009-2008. 2016 It is important for the producer to know the price paid per liter of milk in advance for the best planning of the activity. Since the price of milk received by producers can be increased with the payment of quality bonus for dairy products, taking into account the values of somatic cell count, total bacterial count, protein and fat, leading to greater profitability.